Paclobutrazol effects on cacao seedlings - Valle, Raul R.; Almeida, Alex Alan F. de (Pesquisa Agropecuaria Brasileira, 2014)
The effects of paclobutrazol (2RS, 3RS) -1-(4-Chlorophenyl) - 4,4-dimethyl-2-(1H, 2, 4-triazol- 1 -yl)-pentan-3-ol), ICI PP333 on the morphological characteristics of cacao (Theobroma cacao L.) seedlings were evaluated under greenhouse conditions. The experimental design was a complete randomized design with five treatments and 10 replications. Applications of 5, 15, 45, and 90 ppm of PP333 were made directly to the soil in which 5-months old 'Catongo' cacao seedlings were grown in 5,0 kg poliethylene bags. Plant height was the parameter more affected by the action of PP333. The height reduction by the highest rates was 32% with respect to control plants. The 15 ppm application reduced height by 17% and the 5 ppm did not statistically differ from the control. With the exception of the 90 ppm treatment which significantly reduced stem diameter, the other treatments were not statistically different from the control. Individual leaf area, in the two higher doses, was significantly lower than the control, 0,5, and 15 ppm treatments, by approximately 28%. Total dry weight of plants al the highest rate of PP333 were 21% lower than the control seedlings. Root, stem, and leaf dry weight for the 90 ppm seedlings were 32, 17 and 22% lower than control plants, respectively. The highest dose changed the partitioning of photosynthates, decreasing the root/shoot ratio which was significantly lower.